Blind spots in energy efficiency policies : insights into informational and incentive mechanisms - (:unkn) unknown (My University, 2024)
As global energy demand grows, energy efficiency is critical for reducing consumption and mitigating climate change. Despite widespread implementation, certain energy efficiency policies, particularly in regions with high energy demand like France, face barriers such as market frictions and unreliable informational tools. In rapidly growing energy demand areas like African countries, challenges include nascent policy frameworks and insufficient energy information for consumers to make energy-efficient choices.This thesis examines shortcomings that limit the effectiveness of energy efficiency policies in both high and rapidly growing energy demand regions, focusing on enforcement, reliability, and the role of incentives. It comprises three co-authored chapters, with me as the first author. I investigate energy efficiency labeling and disclosure policies, including France’s Energy Performance Certificate (DPE) and the absence of energy labeling in select African air conditioner (AC) markets, alongside incentive schemes like France’s Certificats d’économies d’énergie (CEE) program.The rise in AC adoption across Africa, driven by rising temperatures, income growth, and urbanization, significantly impacts energy demand and emissions. However, energy efficiency policies in these regions remain understudied, and reliable data on how energy efficiency information is communicated to consumers is lacking. For this first chapter, we compiled a dataset (2019-2022) covering 1,229 AC models from Africa’s largest e-commerce platform across 13 countries. This analysis reveals that less than 10% of AC models provide energy performance information. Weak regulatory enforcement leads to irregular energy efficiency information disclosure, indicating the need for mandatory policies and minimum energy performance standards.In France, the DPE plays a key role in the real estate market and in energy efficiency policies, but it has faced criticism for its complex me
Keywords: African Research